Long-Distance Transport of Prosystemin Messenger RNA in Tomato - Zhang, Haiyan; Hu, Yuanyuan (Frontiers in Plant Science, 2017)
Systemin (SYS) and its precursor protein, prosystemin (PS), are upstream components of the wound-induced signaling pathway in tomato. Although the mobile signal(s) for wound responses has been the subject of considerable research, its identity remains controversial. Intensive studies have revealed the essential role of mRNA on plant systemic signaling. We hypothesize that PS mRNA comprises the transmissible signal in tomato. Herein, we demonstrated that PS mRNA occurs in leaves located at considerable distances from the initial site of its generation by a transient Agrobacterium-infiltration assay system. We also showed that the translocated PS mRNA can be translated into protein. Our results indicate that PS mRNA may be functional as a long-distance signal to modulate systemic defense responses in tomato, providing novel insights into the multifaceted systems by which SYS signaling transports.